Follow me to San Francisco - Caden, Jeffrey; Griffin, Suzanne; Hamilton, Kim; British Broadcasting Corporation (London : BBC English, 1981)
A course about the language and behaviour of people in the United States of America. It shows the things that happen to many people who meet Americans or go to the United States for the first time
Keywords: English language -- Study and teaching